(In press) Spousal Support Predicting Marital Satisfaction Among Parents of Children with Disabilities - Gozali, Vanesa Aprilia (Indonesian Journal of Disability Studies, 2026)
The presence of children with disabilities introduces unique challenges that significantly impact family dynamics, particularly marital satisfaction. Caregiving responsibilities often reduce the time married couples spend together, thereby influencing their marital satisfaction. Research indicates that spousal support whether emotional, appraisal, instrumental, or informational is a key predictor of marital satisfaction. This study examines the role of spousal support as a predictor of marital satisfaction among parents of children with disabilities. Employing a non-experimental quantitative approach with purposive sampling, the research involved 166 married couples with at least one child with disabilities living at home. Participants completed the ENRICH Marital Satisfaction Scale and the Receipt of Spousal Support Scale. Results indicate that spousal support significantly influences marital satisfaction (p < 0.05), with emotional concern being the strongest contributing factor. This research contributes to the literature on the importance of spousal support in enhancing marital satisfaction.